Grain boundary and microstructure engineering of Inconel 690 cladding on stainless-steel 316L using electron-beam powder bed fusion additive manufacturing. Issue 2 (February 2019) - Segura, I.A.; Murr, L.E.; Terrazas, C.A.; Bermudez, D.; Mireles, J.; Injeti, V.S.V.; Li, K.; Yu, B.; Misra, R.D.K.; Wicker, R.B.
Abstract: This research explores the prospect of fabricating a face-centered cubic (fcc) Ni-base alloy cladding (Inconel 690) on an fcc Fe-base alloy (316 L stainless-steel) having improved mechanical properties and reduced sensitivity to corrosion through grain boundary and microstructure engineering concepts enabled by additive manufacturing (AM) utilizing electron-beam powder bed fusion (EPBF). The unique solidification and associated constitutional supercooling phenomena characteristic of EPBF promotes [100] textured and extended columnar grains having lower energy grain boundaries as opposed to random, high-angle grain boundaries, but no coherent {111} twin boundaries characteristic of conventional thermo-mechanically processed fcc metals and alloys, including Inconel 690 and 316 L stainless-steel. In addition to [100] textured grains, columnar grains were produced by EPBF fabrication of Inconel 690 claddings on 316 L stainless-steel substrates. Also, irregular 2–3 μm diameter, low energy subgrains were formed along with dislocation densities varying from 10 8 to 10 9  cm −2, and a homogeneous distribution of Cr23 C6 precipitates. Precipitates were formed within the grains (with ∼3 μm interparticle spacing), but not in the subgrain or columnar grain boundaries. These inclusive, hierarchical microstructures produced a tensile yield strength of 0.527 GPa, elongation of 21%, and Vickers microindentation hardness of 2.33 GPa for the Inconel 690 cladding in contrast to a tensile yield strength of 0.327 GPa, elongation of 53%, and Vickers microindentation hardness of 1.78 GPa, respectively for the wrought 316 L stainless-steel substrate. Aging of both the Inconel 690 cladding and the 316 L stainless-steel substrate at 685 °C for 50 h precipitated Cr23 C6 carbides in the Inconel 690 columnar grain boundaries, but not in the low-angle (and low energy) subgrain boundaries. In contrast, Cr23 C6 carbides precipitated in the 316 L stainless-steel grain boundaries, but not in the low energy coherent {111} twin boundaries. Consequently, the Inconel 690 subgrain boundaries essentially serve as surrogates for coherent twin boundaries with regard to avoiding carbide precipitation and corrosion sensitization.